2021
DOI: 10.1186/s12887-020-02473-3
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient status and associated factors of adiposity in primary school children with normal and high body fat in Colombo municipal area, Sri Lanka

Abstract: Background The prevalence of obesity and associated risk of chronic diseases are increasing among the paediatric population. The effectiveness of preventive measures and interventions are likely to improve when all factors which associate with obesity in a specific target group are considered. Currently such comprehensive data is unavailable for Sri Lankan children aged 8–9 years. Methods This paper pertains to the data collected from August-2015 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 66 publications
3
20
0
Order By: Relevance
“…Of those, 22 articles met our inclusion criteria; one article was excluded because the mean and SD of body fat percentage were considered biologically not plausible [ 26 ]. Finally, 21 articles were included in the systematic review and meta-analysis [ 27 47 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those, 22 articles met our inclusion criteria; one article was excluded because the mean and SD of body fat percentage were considered biologically not plausible [ 26 ]. Finally, 21 articles were included in the systematic review and meta-analysis [ 27 47 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Then, fat and leptin dimorphism between girls and boys, could arise as consequence of physical activity level or sedentary time. It should be mentioned that among the articles that were selected, only three studies reported physical activity levels, though without specifying by sex [ 33 , 40 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the associations were in opposite directions (direct associations for plasma Cu and inverse associations for Se). Published studies were also contradictory for plasma trace elements and anthropometric variables, reporting inverse, null, or direct relationships depending on the population [ 121 , 126 , 148 , 153 , 154 , 162 , 165 , 166 , 167 , 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children 8-9 years old (n = 160) with high body fat (BMI Z-score > 1) in Sri Lanka. [63] Insufficiency in patients with peripheral (16.9%) and central (10.7%) adiposity.…”
Section: Ironmentioning
confidence: 99%
“…Children 8-9 years old (n = 160) with high body fat (BMI Z-score > 1) in Sri Lanka. [63] Calcium Hormone secretion, intracellular signaling, blood clotting, muscle contraction, gene expression, and bone mineralization [67,68] [50]…”
Section: Magnesiummentioning
confidence: 99%